2019
DOI: 10.32413/pjph.v9i1.237
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge About Hiv and Discriminatory Attitudes Toward People Living With Hiv in Pakistan

Abstract: Background: Little evidence is available regarding knowledge about HIV and attitudes of the general population toward PLHIV in Pakistan. Secondary analysis of data from PDHS 2012-13 was performed to evaluate the effect of knowledge about HIV on discriminatory attitudes toward PLHIV in Pakistan and to explore their association with socioeconomic and demographic variables. Methods: Ever-married persons age 15-49 who had ever heard about AIDS were included in the study. Variables measuring composite knowledge and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
23
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 23 publications
20
23
2
1
Order By: Relevance
“…These results are consistent with previous research conducted in South India, where most of the respondents had good knowledge about HIV/AIDS and had positive attitudes towards PLWHAs [43]. Similarly, studies conducted in Karachi (Pakistan) [44] and across Pakistan [16] also reported good knowledge about HIV/AIDS among respondents. Nonetheless, these results also highlight the gaps in women’s knowledge and non-discriminatory attitude towards PLWHAs, which needs to be addressed.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are consistent with previous research conducted in South India, where most of the respondents had good knowledge about HIV/AIDS and had positive attitudes towards PLWHAs [43]. Similarly, studies conducted in Karachi (Pakistan) [44] and across Pakistan [16] also reported good knowledge about HIV/AIDS among respondents. Nonetheless, these results also highlight the gaps in women’s knowledge and non-discriminatory attitude towards PLWHAs, which needs to be addressed.…”
Section: Discussionsupporting
confidence: 90%
“…Women’s overall knowledge about HIV/AIDS and their attitudes towards PLWHAs are the outcome variables for this research. Both variables were inferred from a series of questions used in the PDHS 2012–13 questionnaire [39], consistent with previous similar studies [16, 40] and also aligned with the global AIDS monitoring indicators of 2018 [27]. All the women who had ever heard of HIV/AIDS further responded to questions on their knowledge and attitudes towards PLWHAs.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, participants who had a score of 3-5 were regarded as having high HIV/AIDS knowledge, while those who had a score of 0-2 were considered as having low knowledge. The construction of the overall HIV/AIDS knowledge variable has been published previously [14][15][16].…”
Section: Outcome Variablementioning
confidence: 99%
“…Os enfermeiros encontram-se na linha da frente para a prevenção do VIH/SIDA e são elementos chave no cuidar destes clientes (Bernhed, Mollstedt, & Rosengren, 2018). Estudos anteriores mostraram que a educação relativa ao VIH/SIDA reduziu as atitudes negativas em relação às pessoas que vivem com VIH/SIDA (Genberg, Hlavka, Konda, et al, 2009;Suominen, Laakkonen, Polukova, et al, 2015;Khan, Bilal, & Siddiqui, 2017;Feyissa, Lockwood, Woldie, Munn, 2019). A capacitação através de um conhecimento sólido e atitudes saudáveis faz com que as competências aprendidas ultrapassem o mero desenvolvimento profissional e sejam úteis para tomadas de decisão individual ao nível da vida pessoal e social.…”
Section: Introductionunclassified